1996
DOI: 10.1007/bf00123359
|View full text |Cite
|
Sign up to set email alerts
|

Limits of titin extension in single cardiac myofibrils

Abstract: Passive force and dynamic stiffness were measured in relaxed, single myofibrils from rabbit ventricle over a wide range of sarcomere lengths, from approximately 2-5 microns. Myofibril stretch up to sarcomere lengths of approximately 3 microns resulted in a steady increase in both force and stiffness. The shape of the length-force and the length-stiffness curves remained fully reproducible for repeated extensions to a sarcomere length of approximately 2.7 microns. Above this length, myofibrillar viscoelastic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 38 publications
3
34
0
Order By: Relevance
“…After the 60-s interval, the microscope camera captured the image of the fiber for analysis of sarcomere length and fiber width, using the methods described above. This time interval allowed the restoring force to reach a peak and decay to a relatively constant plateau as described previously (15,32). In pilot studies within this laboratory, 60 s were sufficient to allow plateau tension to be achieved (Fig.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…After the 60-s interval, the microscope camera captured the image of the fiber for analysis of sarcomere length and fiber width, using the methods described above. This time interval allowed the restoring force to reach a peak and decay to a relatively constant plateau as described previously (15,32). In pilot studies within this laboratory, 60 s were sufficient to allow plateau tension to be achieved (Fig.…”
Section: Methodsmentioning
confidence: 77%
“…Titin is a giant protein with a molecular mass of Ͼ3,000 kDa whose molecules span from the Z disk to the M line of the muscle sarcomere (11), and it is abundant in skeletal muscle cells. In animal models, it has been shown that muscle cells can modulate their stiffness by selective expression of different isoforms of titin (9,15,32), but the evidence as to whether the skeletal muscle of human diaphragm can modulate its titin expression into more than one isoform under different conditions is scarce. Using SDS-agarose gels, we have demonstrated that there is a difference in the titin molecule in the diaphragm muscle of COPD patients compared with non-COPD control patients, seen as a difference in the migration of titin bands between the two groups (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the majority of passive tension developed by cardiac tissue at low sarcomere length extensions has been attributed to the intracellular elastic protein titin (14,44). Ca 2ϩ -dependent titin-actin interactions (15,26,41), as well as Ca 2ϩ -sensitive molecular domains within titin (12,23), are reported to modulate passive stiffness. Thus the possibility exists that BDM modifies these interactions and results in the frequency-dependent alterations of dynamic stiffness observed in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Granzier and Irving (17) performed axial extensions of skinned cardiac myocytes from the rat and found no evidence of strain softening between SLs of 1.85 and 2.4 m. Upon axial extension, isolated rabbit (29) and rat (27) myofibrils have demonstrated strain softening, but only when the SL was extended above 3 m. Because the skinning process removed the entire extracellular matrix and collagen, Linke et al (28) attributed the resulting development of passive force and strain softening at large extension to titin.…”
Section: Strain Softeningmentioning
confidence: 99%
“…Both these studies reported strain softening well within the physiological range. Linke et al (27) found strain softening in isolated rabbit cardiac myofibrils but only at sarcomere length (SL) extensions above 2.7 m, which is greater than the normal physiological SL extension. Because all of the collagen had been removed, this strain softening was attributed to titin being nonreversibly altered.…”
mentioning
confidence: 99%